The Green Economy in Market-Oriented Countries: The Case of Kazakhstan - NURGALIYEVA, Kuralay Orazgalievna; AMIROVA, Ainur Uyizbaevna; NURTAZINOVA, Akbayan Serikovna (Journal of Environmental Management and Tourism; Vol 9 No 5 (2018): JEMT Volume IX Issue 5(29) Fall 2018DO - 10.14505//jemt.9.5(29).14, 2019)
A social market economy is predicated on the principle that sustainable development is possible only if there is a solid focus on key economic, social, and environmental issues. The purpose of the research reported in this paper is to explore the outcomes of market reforms related to the shift to a green economy in the Republic of Kazakhstan. The findings from the authors’ study indicate that today the Kazakh economy is one of the world’s most energy-intensive economies, which is due to the use of outmoded infrastructure, technology, and standards, most of which were inherited from as early as the Soviet period. As a result of its market reforms, Kazakhstan has experienced tangible economic growth, but the nation’s environmental indicators remain a serious concern in relation to the health of its citizens. In the Environmental Performance Index (EPI), Kazakhstan has fallen far behind not only most developed market-oriented countries but some of the developing nations that used to be part of the former Soviet Union as well, like Russia, Belarus, Armenia, Turkmenistan, and others. To galvanize the process of shifting to a “green” economy in the Republic of Kazakhstan, it may help to implement some of the new instruments that have been employed as part of environmental policy in certain market-oriented countries and have proven to be efficient. These instruments and approaches include environmental taxes and levies, permit trading systems, deposit return systems, environmentally motivated subsidies, and organizations and enterprises displaying a willing, voluntary attitude toward improving their environmental performance.